1996
DOI: 10.1056/nejm199610033351401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pravastatin on Coronary Events after Myocardial Infarction in Patients with Average Cholesterol Levels

Abstract: These results demonstrate that the benefit of cholesterol-lowering therapy extends to the majority of patients with coronary disease who have average cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
3,253
12
139

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,778 publications
(3,472 citation statements)
references
References 30 publications
(36 reference statements)
68
3,253
12
139
Order By: Relevance
“…Adults with clinical CHD have a ≥26% 10‐year risk of another CHD event. Patients with CHD risk equivalent status, excluding diabetes mellitus,6 have a 10‐year CHD risk of >20% 20, 30, 31. Respective risks of 26% and 21% were multiplied by 1.5, which assumes ASCVD 10 event rates were 50% greater than 10‐year CHD risk alone.…”
Section: Methodsmentioning
confidence: 99%
“…Adults with clinical CHD have a ≥26% 10‐year risk of another CHD event. Patients with CHD risk equivalent status, excluding diabetes mellitus,6 have a 10‐year CHD risk of >20% 20, 30, 31. Respective risks of 26% and 21% were multiplied by 1.5, which assumes ASCVD 10 event rates were 50% greater than 10‐year CHD risk alone.…”
Section: Methodsmentioning
confidence: 99%
“…the excess of diabetes cases with statin therapy first noticed in the JUPITER trial 47 was found to be smaller in the other statin trials 48 ) or may not even be real (e.g. the small excesses of incident cancer cases in the CARE and PROSPER trials 49,50 were not confirmed by the much larger numbers of cases in the other statin trials 51,52 ).…”
Section: Value Of Meta-analyses Of Randomized Trialsmentioning
confidence: 95%
“…31,51 In a large database analysis, a few years of statin therapy was associated with a 15% proportionally lower rate of cancer-related mortality after adjustment for the potential confounding factors that had been recorded 90 and, in some other observational studies, 136 with as much as a halving in colon cancer incidence and in prostate cancer mortality. 137,138 By contrast, there were small excesses of incident breast cancer in the CARE trial 49 and of incident cancer at all sites in the PROSPER trial among patients who were randomized to receive statin therapy. 50 However, based on more than 10,000 cases of incident cancer in the CTT meta-analyses (including CARE and PROSPER), there were no apparent effects -either overall or at any particular site -during an average of 5 years of statin therapy ( Figure 7).…”
Section: Lack Of Effects On Non-vascular Mortality and Cancermentioning
confidence: 96%
“…However, most studies that have supported a “lower is better” linear relationship between LDL cholesterol and outcomes have been conducted in younger populations. Indeed, elderly populations have been significantly under‐represented in statin and PCSK‐9 inhibitor outcome trials 5, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Our study suggests that the linear “dose‐dependent” relationship between LDL cholesterol and outcomes may not apply to elderly populations on statins following ACS hospitalizations, and the effectiveness of using aggressive LDL cholesterol targets among such elderly subpopulations may be unwarranted.…”
Section: Discussionmentioning
confidence: 91%